المدخل إلى علم الاكتناه الحديثي = Introduction to hadith manuscripts, palaeography and codicology - Jamil, Khairil Husaini (2019)
The paper consists of an introductory section and pages from several works pertaining to hadith manuscripts, palaeography and codicology.